Análisis de la estructura de red de la Empresa Danica Fruits S. A. en la ciudad de Baba. - Olvera Macías, Daniela Marisol (2022)
Current LAN and WAN management allows companies and organizations to optimize the use of resources through a centralized network that allows fast and secure information delivery. The present study seeks to know, analyze and recommend actions to solve the existing problems. Integrating the acquired knowledge to optimize the network infrastructure implemented in Danica Fruits S.A. company. After the analysis, the importance of security, control and maintenance required by a network at enterprise level was defined. By applying these protocols, a higher performance will be obtained and, therefore, there will be less risks for the network to be intervened by cybercriminals.